Antidepressants and antipsychotics classified with torsades de pointes arrhythmia risk and mortality in older adults ‐ a Swedish nationwide study. (11th January 2016) - Danielsson, Bengt; Collin, Julius; Jonasdottir Bergman, Gudrun; Borg, Natalia; Salmi, Peter; Fastbom, Johan
Abstract : Aim: The aim of the study was to examine mortality risk associated with use of antidepressants and antipsychotics classified with torsades de pointes (TdP) risk in elderly. Methods: A matched case–control register study was conducted in people 65 years and older dying outside hospital from 2008–2013 ( n = 286 092) and matched controls ( n = 1 430 460). The association between prescription of antidepressants and antipsychotics with various TdP risk according to CredibleMeds (www.crediblemeds.org ) and all‐cause mortality was studied by multivariate conditional logistic regression adjusted for comorbidity and several other confounders. Results: Use of antidepressants classified with known or possible TdP risk, was associated with higher adjusted risk for mortality (OR 1.53, 95% CI 1.51, 1.56 and OR 1.63, 95% CI 1.61, 1.67, respectively) compared with antidepressants classified with conditional TdP risk (OR 1.25, 95% CI 1.22, 1.28) or without TdP classification (OR 0.99, 95% CI 0.94, 1.05). Antipsychotics classified with known TdP risk were associated with higher risk (OR 4.57, 95% CI 4.37, 4.78) than antipsychotics with possible risk (OR 2.58, 95% CI 2.52, 2.64) or without TdP classification (OR 2.14, 95% CI 2.03, 2.65). The following risk ranking was observed for commonly used antidepressants: mirtazapine > citalopram > sertraline > amitriptyline and for antipsychotics: haloperidol > risperidone >olanzapine > quetiapine. Conclusion: The CredibleMeds system predicted drug‐associated risk for mortality in the elderly at the risk class level. Among antipsychotics, haloperidol, and among antidepressants, mirtazapine and citalopram, were associated with the highest risks. The results suggest that the TdP risk with antidepressants and antipsychotics should be taken into consideration when prescribing to the elderly.